Sharing health-care records over the Internet - GRIMSON, JANE BARCLAY (IEEE, 2001)
Presents a novel approach to sharing electronic health-care records that leverages the Internet and the World Wide Web, developed as part of two European Commission-funded projects, Synapses and SynEx. The approach provides an integrated view of patient data from heterogeneous, distributed information systems and presents it to users electronically. Synapses and SynEx illustrate a generic approach in applying Internet technologies for viewing shared records, integrated with existing health computing environments. Prototypes have been validated in a variety of clinical domains and health-care settings.
PUBLISHED
Keywords: Internet; SynEx; Synapses; clinical domains; electronic health-care; record sharing; health computing environments; heterogeneous distributed information systems; patient data